2006
DOI: 10.1128/jvi.00243-06
|View full text |Cite
|
Sign up to set email alerts
|

The Double-Stranded RNA Binding Protein 76:NF45 Heterodimer Inhibits Translation Initiation at the Rhinovirus Type 2 Internal Ribosome Entry Site

Abstract: Eukaryotic mRNA translation regulation is most often achieved by interference with initiation events (10). Unimpeded initiation occurs upon assembly of eukaryotic initiation factor 4F at the cap, recruitment of the 43S preinitiation complex, scanning, formation of the 48S initiation complex at the initiation codon, and 60S ribosomal subunit joining. Translation initiation repressors binding to 5Ј and 3Ј untranslated regions (UTR) have been reported to interfere with distinct steps of the initiation cascade. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(125 citation statements)
references
References 50 publications
7
115
3
Order By: Relevance
“…NF90 was shown to inhibit replication of a broad range of viruses and to form complexes with NF45 and shuttle between the nucleus and cytoplasm (13)(14)(15)(16)(17)(18)(19). However, a detailed mechanism describing how NF90 negatively regulates virus replication remains unclear.…”
Section: Nf90 Is a Component Of Stress Granulesmentioning
confidence: 99%
See 1 more Smart Citation
“…NF90 was shown to inhibit replication of a broad range of viruses and to form complexes with NF45 and shuttle between the nucleus and cytoplasm (13)(14)(15)(16)(17)(18)(19). However, a detailed mechanism describing how NF90 negatively regulates virus replication remains unclear.…”
Section: Nf90 Is a Component Of Stress Granulesmentioning
confidence: 99%
“…It suppresses the function of Ebola virus polymerases through interaction with VP35 (14), inhibits HIV replication through interaction with HIV-1 TAR RNA (15,16), represses internal ribosome entry sites in rhinoviruses (17,18) and negatively regulates influenza virus replication through interaction with viral nucleoprotein (NP) (19). However, other studies (20)(21)(22)(23) found that NF90 is required for the replication of some positivestranded RNA viruses and is important for expression of E6 protein in human papillomavirus-infected cells.…”
mentioning
confidence: 95%
“…For instance, the nuclear protein FBP2 is a KH protein that shuttles to the cytoplasm in infected cells negatively regulating EV71 IRES activity (Lin et al, 2009a). The double stranded RNA-binding protein DRBP76:NF45 is also a nuclear heterodimeric protein that interacts with HRV IRES repressing its activity in neuron-derived cells (Merrill and Gromeier, 2006). Similarly, the cellular mRNA decay protein AU-binding factor (AUF1) behaves as a negative regulator of EV71 and HRV infections .…”
Section: Itafs Dowregulating Ires Activitymentioning
confidence: 99%
“…Nevertheless, NF45 and NF90 were shown to bind to dsRNA as well as to proteins [26,39]. In neuronal cells, the NF45/DRBP76 heterodimer complex can inhibit translational initiation by binding to the 5'UTR of human rhinovirus type 2 that encoding the internal ribosome entry site (IRES) [40]. NF90 has been shown to increase the half-life of IL-2 mRNA following T-cell activation [41].…”
Section: Discussionmentioning
confidence: 99%